Pengaruh Senam Hamil terhadap Penurunan Nyeri Punggung pada Ibu Hamil Trimester II dan III di Wilayah Kerja UPTD Puskesmas Wanaraya - Alvin Ni’matul Azizah; Yuliastuti, Erni; Jannatul Laili, Fitria; Kirana, Rita (Bunda Edu-Midwifery Journal (BEMJ), 2026)
Introduction: Back pain is a common discomfort experienced by pregnant women in the second and third trimesters. It is caused by the growth of the uterus and fetus as well as postural changes that lead to the stretching of ligaments and muscles supporting the spine. A preliminary study conducted by the researcher in the working area of The Public Health Center of Wanaraya in August 2025, found that there were 59 second and third trimesters pregnant women, 37 of whom (62.71%) complained of back pain. Objective: This study aimed to analyze the effect of prenatal exercise on reducing back pain among second and third trimesters pregnant women in the working area of The Public Health Center of Wanaraya. Methods: This study used quantitative analytic research with a pre-experimental one-group pretest-posttest design. The population in this study was 59 pregnant women. The sample was taken using the purposive sampling technique, resulting in 30 pregnant women in the second and third trimesters who experienced back pain. The independent variable was the prenatal exercise. The dependent variable was the back pain in pregnant women. Data were analyzed using the Wilcoxon Signed Rank Test with a significance (α) is 0.05. Results: The study results obtained a p-value of 0.000. this showed that there was a significant effect of prenatal exercise on reducing back pain in pregnant women Conclusion: Prenatal exercise was effective in reducing the intensity of back pain in pregnant women. It was recommended that health personnel at the Public Health Center implement this exercise as part of health promotion efforts to minimize back pain discomfort, improve the quality of life, and enhance the mobility of pregnant women.